Kajian Teknis Sistem Penyaliran Pada Tambang Terbuka Batubara Pit 1 PT. Banjar Bumi Persada - Muhammad Muharrom Muhajirin (Jurnal Teknologi Berkelanjutan, 2022)
This technical study aims to determine the volume of the sump, the length of the material deposition process in the settling pond area, and the right time for dredging the settling pond. Analysis of rainfall data for 2012 – 2021 using the Log Pearson III method obtained a rainfall intensity of 13.77 mm/hour. The catchment area at the study site is divided into three catchment areas (DTH): DTH I = 0.41 km2, DTH II = 0.05 km2, and DTH III = 0.03 km2. The discharge of runoff water in each DTH is as follows: DTH I = 1.09 m3/second, DTH II = 0.08 m3/second, and DTH III = 0.07 m3/second. The sump volume is calculated based on the amount of water filling the sump with the pump discharge out. The recommended sump volume is 16,321.4 m3. There are two pumps, namely the KSB LCC-H 150-500 pump with an actual pumping rate of 405 m3/hour and the Multiflo CF-48H pump with an actual pumping rate of 180 m3/hour. The two available pumps cannot pump the water in the sump to the fullest. Thus, it is necessary to gradually increase the rpm of the KSB LCC-H 150-500 pump to 1,600 rpm so that the discharge increases to 800 m3/hour and replace the Multiflo CF-48H pump unit with a KSB LCC-H 150-500 class pump. Before being channeled into the river, the water from the pumping is clarified in the settling pond. Dredging sediment in settling ponds must be carried out routinely every 45 days.